Safety of furazolidone-containing regimen in Helicobacter pylori infection: a systematic review and meta-analysis. Issue 10 (19th October 2020) - Ji, Chao-ran; Liu, Jing; Li, Yue-yue; Guo, Chuan-guo; Qu, Jun-yan; Zhang, Yan; Zuo, Xiuli
Abstract : Objectives: Furazolidone containing regimen is effectivefor Helicobacter pylori ( H. pylori ) infection, but its safetyremains controversial. To assess the safety of furazolidone containing regimenin H. pylori infection. Design: A systematic review and meta-analysis. Data sources: PubMed, Embase, Cochrane Library, Web of Science and Scopus databases were systematically searched for eligible randomised controlled trials. Eligibility criteria: Studies comparing furazolidone with non-furazolidone-containing regimen, variable durations or doses of furazolidone were included. Data extraction and synthesis: Two reviewers independently selected studies and extracted data. Primary outcomes were the risk of total adverse events (AEs), serious AEs and severe AEs, expressed as relative risk (RR) with 95% CI. Secondary outcomes contained the incidence of individual adverse symptoms, AE-related treatment discontinuation and compliance. Results: Twenty-six articles were identified from 2039 searched records, of which 14 studies (n=2540) compared furazolidone with other antibiotics. The eradication rates of furazolidone-containing regimen were higher than those of other antibiotics in both intention-to-treat (RR 1.06, 95% CI 1.01 to 1.12) and per-protocol analysis (RR 1.05, 95% CI 1.00 to 1.10). Only two serious AEs were reported in furazolidone group (2/1221, 0.16%). No significant increased risk was observed for the incidence of total AEs (RR 1.04, 95% CI 0.89 to 1.21) and severe AEs (RR 1.81, 95% CI 0.91 to 3.60). Twelve studies (n=3139) compared different durations of furazolidone, and four studies (n=343) assessed variable doses. Elevated risk of total AEs and severe AEs were only found in a high daily dose of furazolidone rather than prolonged duration. The incidence of AE-related treatment discontinuation and compliance of patients were all similar, irrespective of dose and duration adjustments. Conclusion: Furazolidone-containing regimen has a similar risk of AEs and compliance as non-furazolidone-containing regimen. A low daily dose of 200 mg is well-tolerated for 14 day regimen and should be first considered. PROSPERO registration number: CRD42019137247